题目内容
计算
(1)-3-5+4;
(2)(-
-
+
)÷
;
(3)8-(-4)÷22+(-3)×(-4);
(4)-14-[2-(-32].
(1)-3-5+4;
(2)(-
3 |
4 |
1 |
2 |
1 |
6 |
1 |
36 |
(3)8-(-4)÷22+(-3)×(-4);
(4)-14-[2-(-32].
(1)原式=-8+4
=-4;
(2)原式=(-
-
+
)×36
=-
×36-
×36+
×36
=-27-18+6
-=-45+6
=-39;
(3)原式=8-(-4)÷4+12
=8-(-1)+12
=8+1+12
=21;
(4)原式=-1-[2-(-9)]
=-1-[2+9]
=-1-11
=-12.
=-4;
(2)原式=(-
3 |
4 |
1 |
2 |
1 |
6 |
=-
3 |
4 |
1 |
2 |
1 |
6 |
=-27-18+6
-=-45+6
=-39;
(3)原式=8-(-4)÷4+12
=8-(-1)+12
=8+1+12
=21;
(4)原式=-1-[2-(-9)]
=-1-[2+9]
=-1-11
=-12.
![](http://thumb.zyjl.cn/images/loading.gif)
练习册系列答案
相关题目